Redetermination of the crystal structure of bis(N-methyl-N-phenyldithiocarbamato- κ2S,S’)copper(II), C16H16CuN2S4 - Onwudiwe Damian C.; Strydom Christien A.; Hosten Eric C. (Zeitschrift für Kristallographie - New Crystal Structures, 2015)
C16H16CuN2S4, monoclinic, P21/n (no. 14), a = 7.6067(2) Å, b = 6.5835(2) Å, c = 18.5042(5) Å, β = 97.2900(10)°, V = 919.2 Å3, Z = 2, Rgt(F) = 0.0243, wRref(F2) = 0.0626, T = 200 K.